Néel-type skyrmion in WTe2/Fe3GeTe2 van der Waals heterostructure - Wu, Yingying; Zhang, Senfu; Zhang, Junwei; Wang, Wei; Zhu, Yang Lin; Hu, Jin; Yin, Gen; Wong, Kin; Fang, Chi; Wan, Caihua; Han, Xiufeng; Shao, Qiming; et al. (Nature communications, 2020)
The promise of high-density and low-energy-consumption devices motivates the search for layered structures that stabilize chiral spin textures such as topologically protected skyrmions. At the same time, recently discovered long-range intrinsic magnetic orders in the two-dimensional van der Waals materials provide a new platform for the discovery of novel physics and effects. Here we demonstrate the Dzyaloshinskii–Moriya interaction and Néel-type skyrmions are induced at the WTe 2 /Fe 3 GeTe 2 interface. Transport measurements show the topological Hall effect in this heterostructure for temperatures below 100 K. Furthermore, Lorentz transmission electron microscopy is used to directly image Néel-type skyrmion lattice and the stripe-like magnetic domain structures as well. The interfacial coupling induced Dzyaloshinskii–Moriya interaction is estimated to have a large energy of 1.0 mJ m −2 . This work paves a path towards the skyrmionic devices based on van der Waals layered heterostructures. Strong magnetic interfacial coupling in van der Waals heterostructures provides a new platform for discovering novel physics and effects. Here, the authors report the formation of skyrmion lattice in the WTe 2 /Fe 3 GeTe 2 van der Waals heterostructure and a Dzyaloshinskii–Moriya interaction with a large energy density of 1.0 mJm −2 .